Immunotherapy in liver cancer: overcoming the tolerogenic liver microenvironment - Liu, Yanju; Yang, Hongyuan; Li, Tian; Zhang, Na (Frontiers in Immunology, 2024)
Liver cancer is a major global health concern, ranking among the top causes of cancer-related deaths worldwide. Despite advances in medical research, the prognosis for liver cancer remains poor, largely due to the inherent limitations of current therapies. Traditional treatments like surgery, radiation, and chemotherapy often fail to provide long-term remission and are associated with significant side effects. Immunotherapy has emerged as a promising avenue for cancer treatment, leveraging the body's immune system to target and destroy cancer cells. However, its application in liver cancer has been limited. One of the primary challenges is the liver's unique immune microenvironment, which can inhibit the effectiveness of immunotherapeutic agents. This immune microenvironment creates a barrier, leading to drug resistance and reducing the overall efficacy of treatment. Recent studies have focused on understanding the immunological landscape of liver cancer to develop strategies that can overcome these obstacles. By identifying the specific factors within the liver that contribute to immune suppression and drug resistance, researchers aim to enhance the effectiveness of immunotherapy. Prospective strategies include combining immunotherapy with other treatments, using targeted therapies to modulate the immune microenvironment, and developing new agents that can bypass or counteract the inhibitory mechanisms in the liver. These advancements hold promise for improving outcomes in liver cancer treatment.